The role of sleep in changing our minds: A psychologist's discussion of papers on memory reactivation and consolidation in sleep - Cartwright, Rosalind D. (Cold Spring Harbor Laboratory Press, 2004)
The group of papers on memory reactivation and consolidation during sleep included in this volume represents cutting edge work in both animals and humans. They support that the two types of sleep serve different necessary functions. The role of slow wave sleep (SWS) is reactivation of the hippocampal-neocortical circuits activated during a waking learning period, while REM sleep is responsible for the consolidation of this new learning into long-term memory. These studies provide further insights into mechanisms involved in brain plasticity. Robeiro has demonstrated the upregulation of an immediate-early gene (IEG zif 268) to waking levels, which occurs only in REM and only in connection with new learning. McNaughton and his group have identified electrical indicators that the hippocampus and neocortex are talking to each other by testing the coactivation of hippocampal sharp wave bursts in SWS and shifts from down to up states of activation in the neocortex. In human studies Smith's group reports work on individual differences such as intelligence and presleep alcohol that affect postsleep performance, and Stickgold and collaborators report that a short nap will improve performance if it contains REM sleep. Payne and Nadel suggest that the recall benefit associated with REM sleep may be due to its association with increased cortisol levels. These papers are important not only in their individual contributions but also in revitalizing the work coordinating waking and sleep. This promises to further the understanding of how our unique capacity to learn from experience and modify our behavior takes place.